A Compararative Study to Evaluate Surgical Site Infections Using Diathermy and Scalpel - Jaikant Paswan; Bijendra Kumar Mishra; V.S. Prasad (International Journal of Health and Clinical Research, 2021)
Background: The use of electrocautery for making skin incisions remains controversial. Aim: Its effect on the rate of Superficial Surgical Site Infection (SSSI) vis-à-vis scalpel use was compared in this study. Methods: A total of 100 patients undergoing open inguinal hernia repair were divided into two: 50 in Electrocautery group, 50 in Scalpel group. Patients were assessed for up to 30 days post-operatively by an assessor blinded to the method used for making skin incision. CDC/NHSN criterion for SSSI was adopted for wound assessment while grading was done using Southampton Wound Grading System. Results: Both groups had comparable mean age (p-value=0.29) and BMI (p-value=0.39). The difference in the incidence of SSSI (5 in Electrocautery, 7 in Scalpel group) on statistical analysis was found to not be significant (p-value=0.53). Conclusion: We conclude that skin incision made with electrocautery is a safe alternative and a convenient method for performing surgeries.